EFFECTS OF DIFFERENT KIND OF SOURCES IN NOISE EXPOSURE: ANTALYA AS A CASE STUDY - Ozkurt, Nesimi; Sari, Deniz; Hamamci, Samet Feyyaz; Tezel, Melike Nese; Erdol, Muhammet; Ece, Mustafa; Yalcindag, Nazli; Yugruk-Akdag, Nese (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2018)
The results of the analyses carried out according to the European Noise Directive for determining the efficacy of different noise sources in areas being exposed to high levels of noise are presented. The study area was selected to cover of all noise sources exposure areas which are critical according to limit values. Comparison of 55 dB(A) and higher noise level impact indicates that road, Antalya airport, and entertainment places are the three noisiest sources of all followed by railway and industrial zones during 24 hrs. time period in Antalya city. 65 dB(A) and higher noise levels for road, Antalya airport, and entertainment places exceeded and their exposed population were 73,300, 9,500, and 2,900 respectively. The violations observed for 75 dB(A) and higher noise levels for road and entertainment places for which exposed population were 17,400, and 700 respectively. The average noise levels sourced from airport, railway, and industrial zones essentially conform to the 75 dB(A) limit for daily time interval. Nearly %10 of population exposed from road noise, %1 both from Antalya airport and entertainment places for 55 dB(A) and higher noise levels during the night time period. However, for railway and industrial zones average noise levels for night time period conformed to the regulatory standards. For 65 dB(A) and higher noise levels, only %3 of population exposed from road noise.
Keywords: Modeling; Noise source; Exposure; Noise map; ROAD-TRAFFIC NOISE; ISTANBUL ATATURK AIRPORT; MYOCARDIAL-INFARCTION; POLLUTION; ANNOYANCE; SLEEP; HYPERTENSION; TURKEY; LEVEL; RISK; Environmental Sciences & Ecology